Pharmacokinetics and safety of moxifloxacin in children with multidrug-resistant tuberculosis - Thee, Stephanie; Garcia-Prats, Anthony J; Draper, Heather R; McIlleron, Helen M; Wiesner, Lubbe; Castel, Sandra; Schaaf, H Simon; Hesseling, Anneke C (Clinical infectious diseases, 2015)
Moxifloxacin is currently recommended at a dose of 7.5-10 mg/kg for children with multidrug-resistant (MDR) tuberculosis, but pharmacokinetic and long-term safety data of moxifloxacin in children with tuberculosis are lacking. An area under the curve (AUC) of 40-60 µg × h/mL following an oral moxifloxacin dose of 400 mg has been reported in adults. In a prospective pharmacokinetic and safety study, children 7-15 years of age routinely receiving moxifloxacin 10 mg/kg daily as part of multidrug treatment for MDR tuberculosis in Cape Town, South Africa, for at least 2 weeks, underwent intensive pharmacokinetic sampling (predose and 1, 2, 4, 8, and either 6 or 11 hours) and were followed for safety. Assays were performed using liquid chromatography-tandem mass spectrometry, and pharmacokinetic measures calculated using noncompartmental analysis. Twenty-three children were included (median age, 11.1 years; interquartile range [IQR], 9.2-12.0 years); 6 of 23 (26.1%) were human immunodeficiency virus (HIV)-infected. The median maximum serum concentration (Cmax), area under the curve from 0-8 hours (AUC0-8), time until Cmax (Tmax), and half-life for moxifloxacin were 3.08 (IQR, 2.85-3.82) µg/mL, 17.24 (IQR, 14.47-21.99) µg × h/mL, 2.0 (IQR, 1.0-8.0) h, and 4.14 (IQR, 3.45-6.11), respectively. Three children, all HIV-infected, were underweight for age. AUC0-8 was reduced by 6.85 µg × h/mL (95% confidence interval, -11.15 to -2.56) in HIV-infected children. Tmax was shorter with crushed vs whole tablets (P = .047). Except in 1 child with hepatotoxicity, all adverse effects were mild and nonpersistent. Mean corrected QT interval was 403 (standard deviation, 30) ms, and no prolongation >450 ms occurred. Children 7-15 years of age receiving moxifloxacin 10 mg/kg/day as part of MDR tuberculosis treatment have low serum concentrations compared with adults receiving 400 mg moxifloxacin daily. Higher moxifloxacin dosages may be required in children. Moxifloxacin was well tolerated in children treated for MDR tuberculosis.